Evaluation of selected aeronautical school libraries through collection mapping - Alay, Hannah Jemaima T. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
An academic library's main purpose is to support its parent institution. This study aimed to evaluate and compare the collection of selected aeronautical libraries; focusing on their curricular support for the degree programs offered by their parent institution.